2021
DOI: 10.3389/fonc.2021.670129
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of Transcription Factors Panel for Digestive System Carcinoma

Abstract: PurposeDigestive system carcinoma is one of the most devastating diseases worldwide. Lack of valid clinicopathological parameters as prognostic factors needs more accurate and effective biomarkers for high-confidence prognosis that guide decision-making for optimal treatment of digestive system carcinoma. The aim of the present study was to establish a novel model to improve prognosis prediction of digestive system carcinoma, with a particular interest in transcription factors (TFs).Materials and MethodsA TF-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…1A–C ). It has been reported that 17 genes play a key role in digestive system tumors, of which three are in the FOX family (FOXD1, FOXM1, and FOXQ1) [ 19 ]. We explored the expression of these three FOX family members in the sorafenib-resistant cells.…”
Section: Resultsmentioning
confidence: 99%
“…1A–C ). It has been reported that 17 genes play a key role in digestive system tumors, of which three are in the FOX family (FOXD1, FOXM1, and FOXQ1) [ 19 ]. We explored the expression of these three FOX family members in the sorafenib-resistant cells.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, the genes of the CREB family behave differently, most of which have a tumor-suppressing nature like the gene CREB3L3 , which is identified as a low-risk gene having high expression in the case of bladder cancer ( 28 ). It was also found that high expression of CREB3L3 helps in the bad prognosis of gastric cancer ( 29 ). It might be possible that this gene, being a low-risk gene, prevents KIRC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Dewaele et al illustrated that EWSR1-CREB3L3 gene fusion is associated with a mesenteric sclerosing epithelioid fbrosarcoma [48]. In GC, CREB3L3 is related to the OS derived from univariate and multivariate Cox regression analysis and is highly expressed in cancer tissues [49]. In a word, the four biomarkers can afect the occurrence and development of cancer in various degrees, including GC, and the guiding signifcance is great to analyze the relationship between the prognosis model and the survival of GC patients.…”
Section: Discussionmentioning
confidence: 99%